Genetic divergence studies in little millet (Panicum sumatrense Roth. ex. Roem. & Schult) using D2 statistics and molecular markers - Kinal Patel, Arna Das*, Dhrumi Dalsaniya, Hadassah Mamidipalli, Sanjith Vasala and Harshal E. Patil2 (Electronic Journal of Plant Breeding)
Little millet is well known for abiotic stress tolerance and high nutritional value. Focused research can bring this crop into mainstream cultivation with good economic return. In kharif, 2021, fifty little millet genotypes were assessed for genetic variation and diversity for 16 quantitative traits. Variability parameters revealed considerable variation among the genotypes for all the traits studied. Phenotypic parameters being higher than genotypic ones indicated only little environmental influence which was confirmed from high heritability and genetic advance. Most of the traits were found to be expressed additively. D2 technique and analysis of 14 polymorphic microsatellite markers offered different clustering pattern indicating that in the present study morphological markers could not be considered true expressers of genotypic variation, but in both the clustering pattern, most IC genotypes were confined in one cluster indicating their relatedness. Moreover, total carbohydrate content was found to be the major contributor towards genetic divergence.